Colloidal Cu-Zn-Sn-Te Nanocrystals: Aqueous Synthesis and Raman Spectroscopy Study - Volodymyr Dzhagan (MDPI AG, 2021)
Cu-Zn-Sn-Te (CZTTe) is an inexpensive quaternary semiconductor that has not been investigated so far, unlike its intensively studied CZTS and CZTSe counterparts, although it may potentially have desirable properties for solar energy conversion, thermoelectric, and other applications. Here, we report on the synthesis of CZTTe nanocrystals (NCs) via an original low-cost, low-temperature colloidal synthesis in water, using a small-molecule stabilizer, thioglycolic acid. The absorption edge at about 0.8–0.9 eV agrees well with the value expected for Cu2ZnSnTe4, thus suggesting CZTTe to be an affordable alternative for IR photodetectors and solar cells. As the main method of structural characterization multi-wavelength resonant Raman spectroscopy was used complemented by TEM, XRD, XPS as well as UV-vis and IR absorption spectroscopy. The experimental study is supported by first principles density functional calculations of the electronic structure and phonon spectra. Even though the composition of NCs exhibits a noticeable deviation from the Cu2ZnSnTe4 stoichiometry, a common feature of multinary NCs synthesized in water, the Raman spectra reveal very small widths of the main phonon peak and also multi-phonon scattering processes up to the fourth order. These factors imply a very good crystallinity of the NCs, which is further confirmed by high-resolution TEM.